Spymaster's prism: the fight against Russian aggression - Devine, Jack (Potomac Books, an imprint of the University of Nebraska Press, 2021)
Our strategic intelligence shortfall-then and now -- Shaping and reshaping the CIA -- A study in Russian spycraft: active measures -- A spymaster president -- Spies among us -- A spymaster's rules in counterintelligence -- Limits of counterintelligence -- Agents-in-place -- Policy spies -- Special activities: an American covert action playbook -- Best practice -- A cautionary tale -- Onward.